Three Responses to Joachimism: Ratzinger, de Lubac, Milbank - Boulter, Matthew R. (Ephemerides theologicae Lovanienses, 2023)
In the words of Eric Voegelin, the modern project of progress aims at nothing less than an 'immanentization of the eschaton' – that is to say, an attempt to make ultimate human perfection present in this world, a perfection of the kind which Christianity associates with the Kingdom of God. Philosophers of history and historians of theology have traced the origins of the idea of a final age of worldly peace and perfection to the writings of a twelfth-century monk, Joachim of Fiore. They have argued that Joachimism is not only unorthodox, but has ultimately led to the worst excesses of modern politics, including communism and fascism. But how dangerous really are Joachim’s ideas? Is a certain type of Joachimism not a legitimate part of a Christian theology of history? This article discusses reactions to Joachimism by three theologians: Joseph Ratzinger, Henri de Lubac, and John Milbank. It turns out that, among the three, Ratzinger is most open to certain aspects of Joachim of Fiore’s thought.